INDUSTRIAL REVOLUTION 4.0: THE PROCESS OF RECRUITING QUALIFIED HUMAN RESOURCES - Fakhriyah, Finna; Adiyanti, Hayu Dwi; Almutazan, Rahman; Saryatmo, Mohammad Agung (International Journal of Application on Economics and Business, 2024)
The Industrial Revolution 4.0 brings changes in all aspects where all access and work involve technology and high optimization using AI and artificial intelligence. The industrial revolution 4.0 is also known as the technological revolution, whereas revolutions 1.0, 2.0, and 3.0 did not use technology. This process also involves changes in human behavior and life patterns. Individuals or human resources in a company must have high quality in line with the changes in the industrial revolution. To get quality human resources, of course, you have to go through a recruitment and selection process until you are selected to join an organization or company. The recruitment process itself currently also involves technology because it adapts to changes in the industrial revolution; this has been happening for a long time, including in Indonesia. The aim of this research is to see the influence of the industrial revolution on the process of conserving quality human resources. The method used is a literature study from previous related research; the journals used are journals from the last 10 years, and then a review process is carried out. Previous research illustrates that by following the industrial revolution, the conservation process will be more effective and efficient, and if companies or organizations do not follow the revolution, it will cause difficulties in obtaining quality human resources. The results of the literature review presented by us no longer need to send applications directly to the office; just send an email, and information about job openings can be obtained via digital and online platforms. This research still has shortcomings due to limited resources and research time. This research provides a contribution to organizations or companies as reference material, and it is hoped that further research can study it more deeply with more and more accurate sources.